Isothiocyanate-modified A3B type zinc phthalocyanine: Synthesis, photophysicochemical characterization, and in vitro evaluation - Ozturk, Ece; Kaplan, Ekrem; Burat, Ayfer Kalkan; Ozcesmeci, Mukaddes; Atmaca, Goknur Yasa; Erdogmus, Ali; Isik, Seyma; Hamuryudan, Esin; Serhatli, Muge (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
In the current study, the synthesis of a novel unsymmetrical zinc phthalocyanine, ZnPc (5), carrying tert-butyl and isothiocyanatophenoxy groups was achieved by the statistical condensation of two different phthalonitriles. Compound 5 was obtained in three steps, starting from tert-butylphthalonitrile and 4-(4-nitrophenoxy)phtha-lonitrile. The isothiocyanate unit was selected to ensure selective bioconjugation under mild reaction conditions and to reduce side product formation, while tert-butyl groups were incorporated to increase solubility and tailor photophysical and photochemical properties relevant to cellular imaging and diagnostic applications. The fluorescence properties and singlet oxygen formation ability of this compound were examined using UV-Vis absorption and fluorescence emission spectroscopy Compound 5 showed a higher singlet oxygen yield than the standard zinc phthalocyanine (0.82 for 5 and 0.67 for the standard). In addition to the photochemical properties, photodynamic therapy (PDT) activity and cellular uptake of compound 5 were investigated. Fluorescence imaging demonstrated efficient cytoplasmic localization of compound 5, while cytotoxicity assays confirmed that no significant dark toxicity or PDT-induced cytotoxicity was observed. These findings indicate that ZnPc (5) is more suitable for cellular imaging and diagnostic applications rather than for PDT treatment.
Keywords: Phthalocyanine; Zinc; Cellular uptake; Fluorescence imaging; Unsymmetric; PHOTODYNAMIC THERAPY; UNSYMMETRICAL PHTHALOCYANINES; PHOTOSENSITIZERS; CONJUGATE; DYES; Chemistry; Crystallography